Enoch Powell and the Conservative Party: Reflections on an Ambiguous Legacy. Issue 3 (28th July 2018) - Peele, Gillian
Abstract: This article examines Enoch Powell's 'Rivers of Blood' speech in relation to the Conservative party. Powell's speech created an additional challenge to a Conservative party already weakened by the loss of the 1964 and 1966 elections and by the failure of the newly elected leader, Edward Heath, to impress his authority decisively on the party. Powell had some parliamentary support but his real following was concentrated in the Conservative grass roots. Powell lost the support of the liberal‐minded Shadow Cabinet; but after 1968 the Conservatives nevertheless moved to the right on the issue, especially after Mrs. Thatcher became leader in 1975. His speech has cast a long shadow as the party has sought to modernise in more recent times and to appeal to a more racially diverse electorate.